Treściowe i językowe wykładniki podejścia do kultu Maryi w protestanckim kazaniu na święto Wniebowzięcia NMP (Artomiusz 1595) = Content-based and language-based indicators of the approach to the worship of Our Lady in the Protestant sermon given on the Day of the Assumption of Mary (Artomius 1595) - Kamper-Warejko, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article addresses the content-based and language-based analysis of the 16th century text titled "Sermon to jest kazanie na dzień Wniebowzięcia Panny czystej (?)" written by Peter Artomius, the priest of Toruń. The aim of the outline is to look at the language-based indicators of the subjective judgement of utterances, to analyse them and to describe possible strategies applied by the author in order to transmit certain content and to defend the principles of faith.
Keywords: dyskurs religijny; mariologia protestancka; apologetyka protestancka; kazanie; Artomiusz, Piotr (1552-1609); 16 w.; religious discourse; Protestant Mariology; Protestant apologetics; sermon; 16th century